2020
DOI: 10.1002/biot.202000015
|View full text |Cite
|
Sign up to set email alerts
|

Separating Empty and Full Recombinant Adeno‐Associated Virus Particles Using Isocratic Anion Exchange Chromatography

Abstract: The development of recombinant adeno‐associated virus (rAAV) gene therapies is becoming an increasing priority in the biotherapeutic landscape. One of the challenges associated with the production of rAAV is the formation of empty AAV particles that do not contain a therapeutic gene. The concerns about the impact of empty particles on clinical safety and rAAV‐mediated gene expression have necessitated the development of purification processes to remove these species. The development of a robust and scalable pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 24 publications
2
64
0
Order By: Relevance
“…In particular, when we applied a step protocol for buffer B, we achieved an almost baseline separation of the full rAAV and the empty capsid peaks. Other studies have also achieved full/empty separation for different AAV serotypes by AEX [ 8 , 24 , 34 , 37 , 38 , 39 , 40 ]. For determination of the degree of separation of full rAAVs from empty capsids, we used analytical AEX.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when we applied a step protocol for buffer B, we achieved an almost baseline separation of the full rAAV and the empty capsid peaks. Other studies have also achieved full/empty separation for different AAV serotypes by AEX [ 8 , 24 , 34 , 37 , 38 , 39 , 40 ]. For determination of the degree of separation of full rAAVs from empty capsids, we used analytical AEX.…”
Section: Discussionmentioning
confidence: 99%
“…Triton X-100 lysates of sf9/BEV and HEK293 cells producing AAV2/8 were obtained from The University of Nantes, Center for Translational Therapy for Genetic Diseases, INSERM UMR 1089, Nantes, France. AAV8 was chosen particularly because AEC is known to separate empty and full capsids into separate peaks [ 6 , 9 , 10 , 16 ]. All were membrane filtered to 0.45 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The 260/280 ratios for empty and full AAV capsids in a non-chromatographic study were reported to be 0.59 and 1.44, respectively [ 7 ]. AEC has been shown to separate empty and full capsids into separate peaks for serotypes 1, 2, 4, 5, 6, 8, and 9 [ 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Empty capsid peaks separated from full capsid peaks by anion exchange (AEC) commonly exhibit ratios in the range of 0.6 to 0.7, while full capsids peaks commonly exhibit ratios in the range of 1.3–1.4.…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange chromatography (AEX) also achieves fractionation of empty and full capsids for many AAV serotypes [4][5][6][7][8][9][10][11][12][13][14][15]. The degree of separation varies among serotypes and does not correlate strictly with DGUC.…”
Section: Introductionmentioning
confidence: 99%